Porous Transport Layers: Exploring the Interface of Skin‐Layered Titanium Fibers for Electrochemical Water Splitting (Adv. Energy Mater. 8/2021). Issue 8 (24th February 2021) - Liu, Chang; Shviro, Meital; Gago, Aldo S.; Zaccarine, Sarah F.; Bender, Guido; Gazdzicki, Pawel; Morawietz, Tobias; Biswas, Indro; Rasinski, Marcin; Everwand, Andreas; Schierholz, Roland; Pfeilsticker, Jason; et al.
Abstract : In article number 2002926, Marcelo Carmo and co‐workers use a very simple and scalable method to protect titanium porous transport layers (PTLs) from passivation by sputtering very thin layers of Ir or Pt onto PTLs. 4000 h stable durability profiles are achieved when PTLs are coated with only 0.1 mg cm −2 of Pt or Ir. The results of this work show how the interface of a well‐protected titanium fiber behaves against passivation after long‐term operation under real electrolysis conditions.